Rationale and design of the expanded combination of evolocumab plus empagliflozin in diabetes: EXCEED-BHS3 trial - Ikaro Breder; Jessica Cunha Breder; Isabella Bonilha; Daniel B. Munhoz; Sheila T. Kimura Medorima; Daniela C. Oliveira; Helison R. do Carmo; Camila Moreira; Anatol Kontush; Francesca Zimetti; Ilaria Zanotti; Luiz Sergio F. Carvalho; et al. (SAGE Publishing, 2020)
Background: Patients with type 2 diabetes mellitus (T2DM) remain at increased cardiovascular residual risk and endothelial dysfunction, even after optimizing metabolic control and treatment by sodium-glucose-2 transporter inhibitors (SGLT2-is). The present study was based on the hypothesis that proprotein convertase subtilisin/kexin 9 inhibitor (PCSK9i) therapy may mitigate endothelial dysfunction in T2DM patients who are on regular treatment by SGLT2-i. Methods: The EXCEED-BHS3 is a prospective, single-center, investigator-blinded, open-label, randomized clinical trial. Participants ( n  = 110) will be randomized (1:1) to either empagliflozin 25 mg/day alone or empagliflozin 25 mg/day plus evolocumab 140 mg every 2 weeks in addition to optimal medical care. The primary endpoint was defined as the change in the 1-min flow-mediated dilation (FMD) after 16 weeks of treatment. The secondary endpoint is the FMD change after ischemia/reperfusion injury protocol (reserve FMD) after 16 weeks of treatment. Exploratory outcomes comprise the change in FMD and reserve FMD after 8 weeks of treatment and the change after 16 weeks of treatment in the following parameters: plasma levels of nitric oxide, vascular cell adhesion molecule-1 and isoprostane, high-density lipoprotein (HDL) and low-density lipoprotein subfractions profile, HDL function, blood pressure, body mass index, waist circumference and adipokines. Conclusion: This will be the first study to evaluate the add-on effect of PCSK9i on endothelial function of T2DM patients under regular use of empagliflozin. Trial registration: ClinicalTrials.gov identifier: NCT03932721